Perubahan Displacement Terhadap Hambatan Kapal Kayu Dengan Kapal Kayu Laminasi, Studi Kasus Kapal Ikan 1gt - Nurhasanah, Muhammad Helmi, Budhi Santoso (Politeknik Negeri Madura, 2017)
Fishermen in Bengkalis is have started selecting the raw materials to become fiberglass for fishing boat. However, until recently the material of wood already there are still many that operate. Fishermen who still have enough wood of ships realize that age is not long compared to fiberglass boats that came the idea to locate the material or an alternative method that can make the wooden boat last longer. The method is carried out by laminating a wooden boat with fiberglass. Wood to be coated fiberglass mix ingredients with the same treatment lamination technique with fiberglass boats. The addition of fiberglass laminate on wood ships will certainly occur many changes in such a wood has change, displacement, Total Resistance, and power of main engine. Intense and previously known displacement of wood is 1,433 Ton and displacement of laminated is 2,004 Tons. While to know the total resistance of the ship and engine power is required, calculated using the method of Van Oortmersen because this method is most appropriate for small fishing vessels by type of fishing boat. Based on the calculation of total resistance, then obtained each change in resistance of wood is 1,14% and 3,6% for laminated of ship.